Medial meniscectomy and anterior cruciate ligament resection result in osteoarthritis in a sheep model - Alfaqeh, Hamoud Hussein Mohammed; Casim, Samsudin Osman; Saim, Aminuddin; Idrus, Ruszymah (2008)
Abstract Objective: This study aims to induce surgical osteoarthritis in a sheep model by excision of the medial meniscus and anterior cruciate ligament of the knee joint. Methods: Osteoarthritis (OA) was induced unilaterally in the knee joint of five adult male sheep by total excision of the medial meniscus and resection of the anterior cruciate ligament (ACL). After a recovery period of 3 weeks, all animals were exercised once daily by running on a hard surface for a distance of 100 meters. Following that the animals were allowed free movement in a confined environment. The animals were sacrificed six weeks after operation. The femoral condyle and the proximal tibial plateau of operated and none operated legs were remove. The interior part of the knee joint was graded according to ICRS grading system. Histological evaluation done by Haematoxylin & Eosin (H&E) and Safranin-O staining. Result: The ICRS grading clearly showed define OA changes as compared to control. H&E staining demonstrated a deep defect on the study area with evidence of inflammation. Safranin-O staining showed absence of cartilage layer. Conclusion: Total excision of meniscus and ACL results in surgically induced osteoarthritis within a short period of time (six weeks) in a sheep model. This study hopes to open new horizons in evaluating treatment for osteoarthritis especially in the area of cell and tissue based therapy.